Development of Diagnostic Test to Measure Learning Loss of High School Students in Trigonometry - Zakhirah, Haura; Suryawati, Suryawati; Ellianti, Ellianti; Mastura, Ayu; Lestari, Mulia (Journal of Mathematics Science and Computer Education, 2024)
Learning loss is when a student loses academic knowledge and skills due to certain situations and conditions, such as pandemics, long school holidays, and other emergencies. An effort can be made to determine the learning loss that occurs in students by using diagnostic tests. However, the availability of questions for diagnostic tests on mathematics, especially trigonometry material, is still limited. This research aims to develop and validate diagnostic test questions to measure high school students' learning loss in the trigonometric function topic. This research uses preliminary research in the development stage with the Plomp model. The stages carried out in this study include self-evaluation and expert review. Document analysis is carried out at the self-evaluation stage by identifying basic competencies and formulating indicators, compiling a learning continuum, formulating attributes, compiling a Q matrix, and constructing questions. Then, three validators tested the validity and feasibility of the questions. The results of the validity test show that the 25 diagnostic questions that have been developed all meet the very valid criteria, with the average score for each item from the three validators being more than 3.20.